Pinanga leonardcoi (Arecaceae), a new species from Mt. Cagua in northeast Luzon, Philippines - Adorador, Jiro T.; Fernando, Edwino S. (Phytotaxa, 2022)
A new species of Pinanga, P. leonardcoi, from Mt. Cagua in northeastern Luzon, Philippines is described and illustrated. This novel palm belongs to the Urosperma group but is unique in having the combination of the following characters: clustered stems with stoloniferous off-shoots, few rachillae (2–3), spirally arranged fruits throughout the rachillae, and fruiting perianth with imbricate calyx lobes. Relevant morphological and ecological notes, and an updated key for the Urosperma group are also included. P. leonardcoi is a narrow-endemic species and is hereby assessed as Critically Endangered.